Insulin resistance and obesity among infertile women with different polycystic ovary syndrome phenotypes - Moamar Al-Jefout (Nature Portfolio, 2017)
Abstract Polycystic ovary syndrome (PCOS) is a common problem among Arab women and is the main cause of infertility due to anovulation. This study investigates insulin resistance (IR) and obesity in different PCOS phenotypes among infertile women (n = 213), of whom 159 had PCOS and 54 women without PCOS, recruited as a control group. Biometric, hormonal and clinical parameters were studied. IR was observed in 133 (83.6%) women with PCOS and in 25 (46.3%) women without PCOS (p < 0.001). IR was significantly associated with PCOS only among women with central obesity (χ2 = 35.0, p < 0.001) and not for the normal category (χ2 = 4.04, p < 0.058). The LH/FSH ratio was not significantly different among the PCOS group (n = 37, 23.3%) compared to the control group (n = 9, 16.7%) (p = 0.308). Among women with PCOS, the most common phenotype was type I (50.3%), with type III (29.6%), type II (14.5%) and type IV (5.7%). Type I had the highest values of fasting insulin (median = 12.98 mU/mL) and HOMA IR values (significant difference among the four phenotypes, p = 0.009 and 0.006, respectively) and is associated with severity of the disease. There was no difference in glucose levels.